Scattering of electromagnetic waves by nearly periodic structures - A. Modinos; V. Yannopapas; N. Stefanou (Physical Review B, 2000)
We present a method, based on the coherent potential approximation, for the treatment of disorder in photonic crystals. We apply the method to the study of light absorption by a three-dimensional array of plasma spheres distributed randomly in a host dielectric medium. We find that the effect of disorder on the absorbance of a thick slab of the material consisting of many layers of spheres is much less pronounced than in the corresponding case of a single layer of spheres.